Exploring extramedullary hematopoiesis: unraveling the hematopoietic microenvironments - Rivera-Torruco, Guadalupe; Muench, Marcus O.; Valle-Rios, Ricardo (Frontiers in Hematology, 2024)
Hematopoiesis is a process by which all blood cells are formed. The mechanisms controlling it have been studied for decades. Surprisingly, while hematopoietic stem cells are among the most extensively studied stem cell types, the complete understanding of how they are regulated during development, adulthood, or in non-homeostatic conditions remains elusive. In this review, our primary focus is on research findings that explore where hematopoietic precursors are found in adults outside their primary niches in the bone marrow. This phenomenon is termed extramedullary hematopoiesis (EMH). Early in development hematopoietic stem cells migrate through different regions within and outside the embryo and later the fetus. Although, the primary home for hematopoietic progenitors is the adult bone marrow, it is now recognized that other adult organs may act as hematopoietic progenitor reservoirs both in mice and humans. The first reports about this topic were principally originated from clinical observations, in cases where the bone marrow was malfunctioning, leading to an aberrant hematopoiesis outside the bone marrow. It is worth highlighting that those extramedullary organs, like the small intestine or fat tissue, contain subsets of fully functioning hematopoietic progenitors demonstrated by both in vitro and in vivo studies. Nonetheless, there are still some unanswered questions regarding the source of these cells, how they differ in function compared to their counterparts in the bone marrow, and the specific roles they play within the tissues where they are located.